Sistem Informasi Inventory Penjualan Barang (Studi Kasus : Toko Aru Raya) - Fahrul Razi (ITB Ahmad Dahlan Jakarta, 2023)
The system for handling product data in a store is one that can facilitate efficient operation. It is still not utilized by the majority of stores, which continue to manage their product data manually. Application for the Goods Data Management System at the Aru Raya Store, which will be sent to the stage of system implementation used to manage transactions at the Aru Raya Store. Numerous flaws in the current system have been discovered during the course of the field research procedure. Despite the fact that there is nothing as a whole, but rather leads to specific issues, it is anticipated to have a significant impact on system users. Because it will be quicker, more accurate, and more precise with this information system, the author of the information system designed the supply chain for Baceno Bag Convection. The author of this new system realized an effective system at Aru Raya Store in Lubuk Begalung by creating it utilizing the PHP, UML, and MySQL Database programming languages.